Suggestive Evidence of Slc2a9 Polymorphisms Association in Gouty Malay Males - Wan Rohani, Wan Taib; Wan Syamimee, Wan Ghazali; Tan, Huay Lin (International Islamic University Malaysia, 2015)
Introduction: Solute carrier family 2, member 9 (SLC2A9) is thought to be an important urate transporter that influences the excretion and reabsorption of serum uric acid, thus has a strong effect on serum urate and risk of gout. SLC2A9 polymorphisms have been extensively studied in various populations in association with gout development. Our aim was to test for association of SLC2A9 SNPs with gout in Malay males.